Cold-water coral mounds in the western Mediterranean Sea: new insights into their initiation and development since the Mid-Pleistocene in response to changes of African hydroclimate - Wienberg, Claudia; Krengel, Thomas; Frank, Norbert; Wang, H.; Rooij, David van; Hebbeln, Dierk (Quaternary science reviews, 2022)
This study presents sediment cores up to 70 m long collected by the sea floor drill rig MARUM-MeBo70 from cold-water coral mounds in the western Mediterranean Sea. From these cores, an unprecedented data set of 200 Th/U coral ages has been obtained, greatly expanding our knowledge of the evolution of Mediterranean coral mounds. The drill records provided new insights into the initiation of the Mediterranean coral mounds as the base of a 60-m-high mound was penetrated and dated to the Mid-Pleistocene (∼390 ka). We also found that mound initiation was non-synchronous as larger mounds possibly initiated already during the Mid-Pleistocene Transition. During the last 480 kyr, mound development occurred in short and intense pulses (duration: ∼10-30 kyr; aggradation rates: 20-275 cm kyr−1), which could not be assigned to ice age-paced oscillations, but showed a remarkably coherent pattern with precession-driven changes in African hydroclimate. Increased dust supply, related to a desertification of the Sahara and northern Africa, appears to have boosted mound development by enhancing productivity conditions (to promote coral growth) and sediment supply (to promote mound aggradation). In addition, mound development is closely linked to the well-ventilated and nutrient-rich Levantine Intermediate Water and internal wave activity associated to this water mass that provided turbulent conditions and enhanced the lateral delivery of food and sediments. During African humid periods, increased freshwater input into the Mediterranean impaired the formation of Levantine Intermediate Water, which most likely resulted in low-energy and oxygen-depleted living conditions for Mediterranean coral communities. This study shows the importance to consider past changes in continental hydroclimate and their implications on oceanic processes to fully understand the complex environmental controls on coral mound development. In the Mediterranean Sea, such land-atmosphere-ocean feedback processes are especially amplified due to its latitudinal placement between two climate regimes, making this basin and its deep-sea ecosystems most vulnerable to past and future climate change.
Gesehen am 17.01.2023